Consumers' optimism bias and responses to risk disclosures in direct-to-consumer (DTC) prescription drug advertising: the moderating role of subjective health literacy - Ahn, Ho-Young (Anthony); Park, Jin Seong; Haley, Eric (Journal of Consumer Affairs, 2014)
Despite a substantial body of research in direct-to-consumer advertising (DTCA) for prescription drugs, what is missing from the existing discussion on the risk disclosure in DTCA is a focus on the roles of individual motivation and ability to process risk information. Guided by the Elaboration Likelihood Model (ELM) and the Motivation-Ability-Opportunity framework, the current study examines the roles of the consumer's optimism bias and subjective health literacy in responding to the risk disclosure in DTCA. By analyzing survey data (N = 404), the study reveals that: (1) consumers who show a tendency to believe that they are at less risk of experiencing adverse reactions to prescription drugs than their peers are less likely to pay attention to the risk disclosure or intend to seek further information about the health risks of drugs, (2) the relationship between optimism bias and information-seeking intentions is stronger for consumers with high subjective health literacy than for those with low health literacy. Implications and recommendations are provided.
26 citations (Crossref) [2023-10-31] tex.eissn: 1745-6606 tex.unique-id: ISI:000333470200008
Keywords: dept.com